Organization of Eastern Carribbean States : Report on the Observance of Standards and Codes - World Bank (Washington, DC, 2012)
This report provides an assessment of accounting, financial reporting and auditing requirements and practices within the enterprise and financial sectors in the Organization of Eastern Caribbean States (OECS). The report uses International Financial Reporting Standards (IFRS) and International Standards on Auditing (ISA) as benchmarks and draws on international experience and good practices in the field of accounting and audit regulation. High-quality financial information supports relevant strategic objectives for the OECS, including: (1) an investor-friendly business climate; (2) sub-regional and regional harmonization; (3) better management and increased transparency of public-interest enterprises; and (4) improved Small and Medium Enterprise (SME) access to credit as an outgrowth of a shift toward lending based on the borrower's financial performance and cash flow. Due to their small size (total population about 560,000) and their tropical island geography, OECS countries face special development challenges, including limited human and institutional capacity, high per capita costs of basic social and infrastructure services, and vulnerability to natural disasters and other external shocks. High levels of indebtedness and fiscal imbalance are additional factors affecting growth and crowding out private investment. These constraints significantly affect the strategic planning and decision-making processes in both the public and private sectors and make capacity issues more significant than in larger countries. The OECS accounting and auditing practices need to be strengthened and modernized to serve adequately the emerging needs of the market and support sustainable economic development.